Dynamic Measurement System for Interchangeable Shock Absorber Test Rig - M. S. M., Sani; M. M., Zainudin (Universiti Malaysia Pahang, 2008)
An automotive suspension system is meant to provide safety and comfort for the occupants. Shock absorber is an important part of automotive suspension system which has an effect on ride characteristics such as ride comfort and driving safety. Basically, this project involves designing the test rig for testing and indicating the condition of shock absorber in automotive vehicle. The test rig is designed and built for testing shock absorber in the area of dynamic, vibration and displacement measurement. The system is capable for 850cc and l 600cc shock absorber interchangeable. Sensor technologies such as accelerometer, displacement sensor's wire and force sensor are applied in order to detect the signal and transfer to data acquisition. The data acquisition system is required to collect measure and analyze data from the test rig.